ANALISIS PENALARAN GEOMETRIS MAHASISWA PENDIDIKAN MATEMATIKA SEMESTER IV DALAM PENYELESAIAN MASALAH SEGITIGA PADA GEOMETRI EUCLID MELALUI REPRESENTASI MOTIF ULOS BATAK. - Maria Florentina Togatorop; Ester Fransiska Nababan; Edwina Pardosi; Muhammad Rasyid Mondol; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students' geometric reasoning in solving triangle problems in Euclid Geometry through the representation of Ulos Batak motifs and identify the types of errors that occur. This study uses a descriptive qualitative approach with the subjects of 15 students in the fourth semester of Mathematics Education. The instrument was in the form of 5 HOTS-based description questions, and the data were analyzed using the Miles and Huberman model and Newman Error Analysis (NEA). The results showed that students' geometric reasoning skills were in the high category, with 80% in the high category and 20% in the medium category, and an average score of 87.4%. The aspects of understanding and transformation are relatively good, while reasoning and connection are still low. The dominant error is interpretation error. Thus, the use of Ulos Batak motifs supports geometry learning, but it needs to be strengthened in the aspects of interpretation and concept connection.